2014
DOI: 10.1111/jcpp.12316
|View full text |Cite
|
Sign up to set email alerts
|

Maladaptive social information processing in childhood predicts young men's atypical amygdala reactivity to threat

Abstract: Background Maladaptive social information processing, such as hostile attributional bias and aggressive response generation, is associated with childhood maladjustment. Although social information processing problems are correlated with heightened physiological responses to social threat, few studies have examined their associations with neural threat circuitry, specifically amygdala activation to social threat. Methods A cohort of 310 boys participated in an ongoing longitudinal study and completed question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 35 publications
2
24
0
Order By: Relevance
“…Youth who were more likely to generate aggressive responses to ambiguous social conflict were rated by their parents and teachers as exhibiting higher levels of CPs. Choe et al (2015) demonstrated similar findings in an independent sample of urban, male, low-income youth, linking ARG in middle childhood to a greater number of criminal arrests in young adulthood. These findings also are consistent with the extensive body of literature indicating that SIP problems in childhood, particularly ARG, have long-standing consequences for adolescents’ CPs (e.g., Hyde et al 2010).…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Youth who were more likely to generate aggressive responses to ambiguous social conflict were rated by their parents and teachers as exhibiting higher levels of CPs. Choe et al (2015) demonstrated similar findings in an independent sample of urban, male, low-income youth, linking ARG in middle childhood to a greater number of criminal arrests in young adulthood. These findings also are consistent with the extensive body of literature indicating that SIP problems in childhood, particularly ARG, have long-standing consequences for adolescents’ CPs (e.g., Hyde et al 2010).…”
Section: Discussionsupporting
confidence: 71%
“…The present findings should also be considered in conjunction with evidence using neuroimaging indicating that regions of the limbic system (e.g., amygdala) and the prefrontal cortex (e.g., ventral prefrontal cortex) are activated as individuals process information in response to interpersonal conflict (Choe et al 2015; Meyer-Lindenberg et al 2006). For example, in an independent sample of 310 racially diverse and low-income men, Choe et al (2015) found that maladaptive SIP patterns at ages 10 and 11 predicted increased left amygdala reactivity to facial expressions of fear at age 20, suggesting hypervigilance to indications of social threat.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Moreover, a recent study reported a positive association between propensity for impulsive aggression and amygdala responses to fearful expressions in a large sample of individuals (n = 310) (Choe et al 2015). However, none of these studies reported either increased responsiveness of the hypothalamus or the PAG.…”
Section: Neurobiology Of Impulsive Aggressionmentioning
confidence: 96%
“…Given the literature briefly reviewed previously, it can be predicted that such patients will show heightened responsiveness in regions implicated in impulsive aggression to emotional provocation (Blair 2001) ; that is, the amygdala, hypothalamus, and PAG (Panksepp 1998;Gregg and Siegel 2001;Nelson and Trainor 2007;Lin et al 2011). In line with this suggestion, patients with posttraumatic stress disorder (PTSD) (Shin et al 2006), intermittent explosive disorder (Coccaro et al 2007), severe mood dysregulation (Thomas et al 2013), and borderline personality disorder (Hazlett et al 2012), as well as impulsively aggressive spouse abusers (Lee et al 2008), all with an increased risk for reactive aggression, all show increased amygdala responsiveness to threatening stimuli relative to comparison FIG. 1.…”
Section: The Acute Threat Responsementioning
confidence: 98%